Bioactive (3Z,5E)-11,20-Epoxybriara-3,5-dien-7,18-olide Diterpenoids from the South China Sea Gorgonian Dichotella gemmacea - Wen Zhang; Ling Li; Yang-Hua Yi; Attila Mandi; Tibor Kurtan; Ming-Ping La; Peng Sun; Bao-Shu Liu; Cui Li; Hua Tang (Marine Drugs, 2011)
Six new (3Z,5E)-11,20-epoxybriara-3,5-dien-7,18-olide diterpenoids, gemmacolides N–S (1–6), were isolated together with four known analogues, juncenolide D, and juncins R, S and U (7–10), from the South China Sea gorgonian Dichotella gemmacea. The structures of the new compounds were elucidated by the detailed analysis of spectroscopic data in combination with the comparison with reported data. The absolute configuration of 1 was determined by a TDDFT calculation of its solution ECD spectrum, affording the determination of absolute configuration of other analogues by simply comparing their ECD spectra with that of 1. The cytotoxic and antimicrobial activities of these compounds were evaluated. In preliminary in vitro bioassays, compounds 4, 5, 6, 8 and 9 showed cytotoxicity against A549 and MG63, while compounds 1, 2, 4, 7–10 showed antimicrobial activity against the fungus Septoria tritici and the bacterium Escherichia coli.